HOSPITAL TOY LIBRARY: PARENTS' PERCEPTION IN THE PEDIATRIC UPA IN ANÁPOLIS - Costa, Cássia Fernanda de Souza; Abreu, Daniele Camargos Vasconcelos; Nascimento, Joelma Passos; Tavares, Larissa Oliveira Tristão; Ferreira, Maria Clemàªncia Pinheiro de Lima (CIPEEX, 2022)
THE HOSPITAL PLAYROOM IS AN AREA FOR HOSPITAL TOYS IN COLLABORATING WITH THE CARE PROCESS, ESPECIALLY FOR CHILDREN, TO HELP BALANCE THE CHILD'S EMOTIONAL STATE (ALMEIDA; FERREIRA, 2017). THIS SUMMARY REFERS TO THE RESULTS OF A QUALITATIVE RESEARCH, CLASSIFIED AS A CASE STUDY OF DEALING WITH A SPECIFIC REALITY: THE PEDEATRIC EMERGENCY CARE UNIT OF ANÁPOLIS - UPA. THE RESEARCH HAD AS GENERAL OBJECTIVE TO ANALYZE THE WORK DEVELOPED IN THE UPA TOY LIBRARY, REGARDING ITS RESULTS AND REPERCUSSIONS FROM THE PERSPECTIVE OF THE PARENTS. THE SPECIFIC OBJECTIVES WERE: TO DESCRIBE HOW THE STRUCTURE OF A HOSPITAL TOY LIBRARY SHOULD BE, TO EXPLAIN THE OPERATION OF THE REFERRED TOY LIBRARY AND TO ANALYZE ASIDE THE PARENTS OF CHILDREN TREATED THERE, WHAT ARE THE BENEFITS THAT, IN THEIR PERSPECTIVE, THE PROPOSAL PROVIDES TO THEIR CHILDREN. THE METHODOLOGY USED WAS A LITERATURE REVIEW FOLLOWED BY FIELD DATA COLLECTION WITH SEMI-STRUCTURED INTERVIEWS WITH 20 PARENTS OR GUARDIANS WHO WERE ACCOMPANYING THE CHILDREN. THE UPA TOY LIBRARY IS CHARACTERIZED BY SERVICE IN THE PHYSICAL SPACE AND IN THE EMERGENCY ROOM BEDS, IN THE SEMI-HOSPITALIZATION REGIME FOR UP TO 24 HOURS. THE UNIT COMPLIES WITH THE PROVISIONS OF LAW NO. 11,104 OF MARCH 21, 2005 (BRASIL, 2005), WHICH ESTABLISHES MANDATORY EXISTENCE OF TOY LIBRARIES IN HOSPITALS THAT OFFER INPATIENT PEDIATRIC CARE. THE FAMILIES SERVED, IN GENERAL, HAVE LOW INCOME AND MAKE USE OF PUBLIC HEALTH SERVICES. THE RESPONSES AND STATEMENTS OF THE PARENTS INDICATE THAT THE PROPOSAL OF THE TOY LIBRARY CONTRIBUTE TO THE PHYSICAL AND EMOTIONAL WELL-BEING OF THE CHILDREN WHO ARE CARED FOR IN THE ESTABLISHMENT AND HELP OVERCOME HOSTILITIES IN A HOSPITAL ENVIRONMENT. THE RESULTS SHOW THAT THE PARENTS' UNDERSTANDING OF THE REPERCUSSIONS OF THE TOY LIBRARY WITH THEIR CHILDREN, PERMEATES THE HUMANIZED TREATMENT THEY RECEIVE FROM THE TEAM OF PEDAGOGUES AND THE SENSITIVITY SHOWN BY THEM, AND IS NOT DIRECTLY LINKED TO THE PSYCHOLOGICAL OR PHYSIOLOGICAL EFFECTS THAT BENEFIT CHILDREN. IN OTHER WORDS, THE RECEPTION RESULTS IN ASPECTS THAT CONTRIBUTE TO THE CARE, HOWEVER, DESPITE WHAT SCIENCE POINTS OUT ABOUT THE POSITIVE IMPLICATIONS OF PLAYFUL ACTIONS IN A HOSPITAL ENVIRONMENT, SUCH AS PHYSIOLOGICAL REACTIONS THAT CONTRIBUTE TO ALLEVIATING FEAR, ANGUISH AND THE SADNESS, WHEN SEEING THEIR CHILDREN WELCOMED BY THE PEDAGOGUES, THE PARENTS REALIZE THAT THE CHILDREN FEEL MORE SECURE AND CALM, AS WELL AS THEMSELVES. THE THEME IS RELEVANT SINCE IT EXPANDS THE UNDERSTANDING OF THE POSSIBILITIES OF PEDAGOGUE'S FIELDS OF ACTION, IN ADDITION TO AN INNOVATIVE PERSPECTIVE IN THE SENSE OF VALIDATING THE NEEDS OF THESE SPACES ACCORDING TO THE AFOREMENTIONED LAW. ALTHOUGH THE ANÁPOLIS PEDIATRIC UPA OPERATES IN AN EMERGENCY ROOM, THE SERVICES PROVIDED BY THE TOY LIBRARY TEAM CERTIFY THE RELEVANCE OF THE THEME AND CAN SERVE AS AN INCENTIVE FOR HEALTH ESTABLISHMENTS IN THE CITY OF ANÁPOLIS AND REGION TO INVEST IN THE CREATION AND ORGANIZATION OF SPACES LIKE THESE, WITH SIGNIFICANT SCIENTIFIC AND SOCIAL IMPACTS.